Two new species of Lasiosyne from the Lower Cretaceous Yixian Formation (Coleoptera, Lasiosynidae). (December 2022) - Guo, Henan; Zhao, Yanchen; Chang, Huali; Shih, Chungkun; Ren, Dong
Abstract: Two new species, Lasiosyne integera sp. nov. and Lasiosyne parva sp. nov., are described from the Lower Cretaceous, Yixian Formation of Huangbanjigou Village, Liaoning Province, northeastern China. These two new fossil species can be assigned to the extinct Mesozoic beetle family Lasiosynidae, based on their elongate suboval body, filiform antenna, striate elytron with lateral edge emarginated at the middle, abdomen with five ventrites, and slightly narrow and simple 5-segmented tarsus. This Mesozoic family was placed in infraorder Elateriformia with a mixture of several characters among superfamilies of Dascilloidea, Elateroidea, Buprestoidea, and Byrrhoidea. These two new species enhance the diversity of the genus Lasiosyne during the mid-Mesozoic. In addition, they also provide additional information for future phylogenetic studies of Lasiosynidae evolution.